2020
DOI: 10.3390/jcm9030841
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Upregulates Angiotensin-Converting Enzyme-2 Receptor: A Potential Adhesion Site for Novel Coronavirus SARS-CoV-2 (Covid-19)

Abstract: The epicenter of the original outbreak in China has high male smoking rates of around 50%, and early reported death rates have an emphasis on older males, therefore the likelihood of smokers being overrepresented in fatalities is high. In Iran, China, Italy, and South Korea, female smoking rates are much lower than males. Fewer females have contracted the virus. If this analysis is correct, then Indonesia would be expected to begin experiencing high rates of Covid-19 because its male smoking rate is over 60% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
467
4
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(520 citation statements)
references
References 35 publications
19
467
4
30
Order By: Relevance
“…States. While we did not find smoking to be significantly influential, Brake et al (2020) emphasize that smoking contributes to the vulnerability of combating COVID-19. Their findings also highlight that smoking may not be limited to traditional cigarettes; other smoking methods and devices are to be further investigated, including electronic cigarettes and waterpipe smoking (Brake et al, 2020).…”
Section: Spatial Error Model (Sem)contrasting
confidence: 97%
“…States. While we did not find smoking to be significantly influential, Brake et al (2020) emphasize that smoking contributes to the vulnerability of combating COVID-19. Their findings also highlight that smoking may not be limited to traditional cigarettes; other smoking methods and devices are to be further investigated, including electronic cigarettes and waterpipe smoking (Brake et al, 2020).…”
Section: Spatial Error Model (Sem)contrasting
confidence: 97%
“…Interestingly, the levels were downregulated to never-smoker levels in former smokers. The results of our analysis are in keeping with several recent reports on ACE2 and smoking (Brake et al, 2020;Leung et al, 2020;Smith and Sheltzer, 2020).…”
Section: Tmprss2 and Ace2 Mrna Expression Increase In Current Smokerssupporting
confidence: 91%
“…Several contrasting findings exist in the literature on ACE2 and cigarette exposure 7681 . In particular, it has been reported that nicotine and/or cigarette smoke has the potential to downregulate ACE2 expression in certain tissues or cell types 7679 .…”
Section: Discussionmentioning
confidence: 96%